2009
DOI: 10.1111/j.1365-2672.2009.04274.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofvanA-typeEnterococcus faeciumisolates from urban and hospital wastewater and pigs

Abstract: Aims:  In this study we analysed urban, hospital wastewater and pig faeces samples to investigate the presence of vancomycin‐resistant Enterococcus faecium strains (VREF) and to determine potential links among the strains originating from the above sources and VREF strains causing clinical infections. Methods and Results:  Urban, hospital wastewater and pig faeces exhibited high VREF prevalence of 52%, 87% and 85%, respectively. Pulsed field gel electrophoresis (PFGE) clustering of VREF genotypes as well as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…Multidrug Resistance Index was observed in this study where 5 isolates had an MDRI ranging from 66 to 83% and 8 isolates had MDRI of 61%. In a study conducted by Kotzamanidis et al (2009), it was observed an AML-CAZ-VA-TE as the most occurring phenotype pattern in isolates from pig farm environment, whereas in this study the most occurring phenotype patterns were P-RL-VA- Table 2. Predominance of multiple antibiotic resistance phenotypes and multidrug resistant index of isolates.…”
Section: Discussioncontrasting
confidence: 52%
“…Multidrug Resistance Index was observed in this study where 5 isolates had an MDRI ranging from 66 to 83% and 8 isolates had MDRI of 61%. In a study conducted by Kotzamanidis et al (2009), it was observed an AML-CAZ-VA-TE as the most occurring phenotype pattern in isolates from pig farm environment, whereas in this study the most occurring phenotype patterns were P-RL-VA- Table 2. Predominance of multiple antibiotic resistance phenotypes and multidrug resistant index of isolates.…”
Section: Discussioncontrasting
confidence: 52%
“…Enterococci are well recognized as AR gene reservoirs and readily transfer genes both intraand inter-specifically [31,38,73]. A number of mobile genetic elements (MGE) such as plasmids and transposons are present in enterococci which facilitate AR gene transfer [31,73].…”
Section: Discussionmentioning
confidence: 99%
“…Waste received from environments under significant antibiotic pressure, such as hospitals, consistently contains a greater proportion of singly and multiple drug-resistant bacteria [9,22,26,28,38,60] and AR enterococci are commonly recovered from sewage [2,8,9,28,38,47,51,55]. House flies and other filth flies often have direct and unhindered access to many steps in the waste processing flow and therefore may acquire bacteria associated with the waste.…”
Section: Introductionmentioning
confidence: 99%
“…The low detection rates of VRE in Japan may be due to a shorter history of the use of avoparcin, a growth promoter for livestock, compared to other countries [33] and the use of lower dosages of VCM clinically than in the US [34]. In European countries, VRE are prevalent in the environment; they were detected in livestock and wastewater treatment plants [35,36]. Several studies indicated that the intensive use of avoparcin as a growth promoter in food animals, such as broilers and pigs has contributed to an increase in VRE [37,38].…”
Section: Discussionmentioning
confidence: 99%